Conspectus Genericus Scorpionorum 1758–1985 (Arachnida: Scorpiones) updated through 2018 - Francke, Oscar F. (Zootaxa, 2019)
Genus and subgenus names introduced for all Recent and fossil scorpions from 1758–2018, are listed. The treatment follows the Conspectus of Francke (1985) and Dupré (2007) with considerable additional information accumulated during intensive scorpiological research of 2006–2018. The list also includes all available generic and subgeneric synonyms, incorrect spellings and unavailable emendations. For Recent taxa the new totals are 19 families compared to only nine in the first Conspectus, 220 genera with an increase of almost 100 from the first version, and 23 subgenera; for fossil taxa there are 43 families and 80 genera, 12 of which are incertae sedis. The type species of all accepted genus-group names are given.